2010
DOI: 10.1021/tx100153w
|View full text |Cite
|
Sign up to set email alerts
|

Alkylating Potential of Oxetanes

Abstract: Small, highly strained heterocycles are archetypical alkylating agents (oxiranes, beta-lactones, aziridinium, and thiirinium ions). Oxetanes, which are tetragonal ethers, are higher homologues of oxiranes and reduced counterparts of beta-lactones, and would therefore be expected to be active alkylating agents. Oxetanes are widely used in the manufacture of polymers, especially in organic light-emitting diodes (OLEDs), and are present, as a substructure, in compounds such as the widely used antimitotic taxol. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
2
4
0
Order By: Relevance
“…Note further that according to a recent investigation, oxetanes do not react with NBP at neutral pH, which is in agreement with our present findings.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Note further that according to a recent investigation, oxetanes do not react with NBP at neutral pH, which is in agreement with our present findings.…”
Section: Resultssupporting
confidence: 94%
“…Twelve oxiranes (A1–A4, A6, A7, B3–B7, and C1) and the three oxetanes (C2–C4) of the present compound set had been tested earlier with respect to their mutagenic potential in bacteria , and in Chinese hamster V79 cells . Accordingly, to check the applicability of the NBP chemoassay to screen chemicals for their mutagenic potential, the results of common mutagenicity screening assays are compared with our presently determined log k NBP values in Figures and ; the respective mutagenicity data are provided in the Supporting Information (Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…These included oxophilic metallic complexes (Y(OTf) 3 and MgCl 2 ⋅6 H 2 O) and organocatalytic promoters (urea and thiourea) (Supporting Information, Figures S6–S21). The inertness of the oxetane ring towards nucleophiles is in line with previous studies that described their lack of geno/cytotoxicity and mutagenicity, unlike that of epoxides and β‐lactones, because they do not act as alkylating agents at physiological pH . Likewise, other proteins such as AnxV reacted similarly at pH 11 with 10 % DMF and expected product 3 was obtained in >95 % conversion, thus demonstrating the robustness of this alkylation protocol to modify this widely used apoptotic protein marker (Figure b).…”
Section: Figuresupporting
confidence: 85%
“…28,29 However, a recent report studying the alkylating ability of oxetane, 3,3-dimethyloxetane, and 3-methyl-3-oxetanemethanol (1) demonstrated that these oxetanes are neither mutagenic nor genotoxic. 30 Furthermore, alkylation of 4-( pnitrobenzyl)pyridine was only observed at acidic pH, implicating that oxetanes do not act as alkylating agents at physiological pH. 30 To assess the systemic toxicity of oxetane-substituted sulfoxide 3, we performed a brine shrimp assay ( Table 4).…”
mentioning
confidence: 99%
“…30 Furthermore, alkylation of 4-( pnitrobenzyl)pyridine was only observed at acidic pH, implicating that oxetanes do not act as alkylating agents at physiological pH. 30 To assess the systemic toxicity of oxetane-substituted sulfoxide 3, we performed a brine shrimp assay ( Table 4).…”
mentioning
confidence: 99%